On The Convergence of Stability Domain on Time Scales - Ha, Nguyen Thu; Nguyen, Khong Chi; Lan, Le Hong (VNU Journal of Science: Mathematics - Physics; Vol 31 No 4, 2015)
This paper studies convergence of the stability domains for a sequence of time scales. It is proved that if the sequence of time scales (Tn) converges to a time scale T in Hausdorff topology then their stability domains UTn will converge to the stability domain UT of T. Keywords : Implicit dynamic equations, time scales, convergence, stability domain, stability radius.